A practical device designed to concentrate cells for cytomorphological studies of biological fluids - Torres Guerra, Enrique (Investigación Clínica, 2013)
Â  In the present work, a device designed for concentrating cells from biological fluids is described. The instrument consists of a tube in which the inner cavity has a conical shape at one of its ends and a small orifice is found at the botton, while the tube's exterior maintains its cylindrical shape. The tube is placed inside a second tube that ends on a flat surface on which a glass cover slide 1s placed. The sample to be studied is placed in the inner tube of the assembled device and spun in a regular clinical centrifuge. Cells are collected on the glass slide, fixed and stained for microscopinal studies. The device was tested using 23 samples of cerebrospinal fluid (CSF) from patients with lymphoproliferative diseases. An adequate number of intact cells was recovered for observation, and a precise diagnosis was possible. Cells from three aliquots of each CSF sample were concentrated by this method, and by the more expensive standard commercial cytocentrifuge, with similar results. The device described here provides an easy, efficient and inexpensive method, for the concentration of cells from organic fluids.